Comparative Evaluation of Herbal and Commercial Toothpaste on Salivary pH and Streptococcus Mutans Count: A Randomized Crossover Clinical Trial - Ebrahimi, Rayan; Peik, Hanieh; Emami , Seyyed Jamal; Salimizand , Himen; Khosravi, Mohammad Rastegar (Journal of Dental School, 2024)
Objectives Enhancing dental health and oral hygiene is essential for preventing dental caries. Recently, there has been significant interest in using natural ingredients in oral care products. This study aimed to compare the effects of herbal toothpaste containing Saqqez oleo-gum resin essential oil with Sensodyne toothpaste on the colony count of Streptococcus Mutans (S. mutans) and salivary pH levels. Methods A randomized double-blinded clinical trial with a crossover design was conducted with 40 students aged 18-35 years who were caries-free. Initially, unstimulated saliva samples were collected to determine the baseline mutans streptococci count and salivary pH levels. In the first phase, participants were randomly divided into two groups: Group I received herbal toothpaste containing Saqqez oleo-gum resin essential oil, while Group II used Sensodyne toothpaste. After supervised tooth brushing, saliva samples were collected again to assess pH levels and S. mutans counts. Following a 72-hour washout period, the procedures were repeated with the groups switching toothpastes according to the crossover design. Data were analyzed using the Mann-Whitney U test and Wilcoxon matched pairs signed-rank test, at a significance level of p<0.05. Results A significant reduction in the S. mutans colony count and a significant increase in salivary pH levels were observed in both groups compared to their baseline values (P<0.05). However, no significant difference was found between the efficacy of the two toothpastes (P>0.05). Conclusion The effect of herbal toothpaste containing Saqqez essential oil on salivary pH and S. mutans level was comparable to that of commercial toothpaste evaluated in this study.